Mothering while black boundaries and burdens of middle-class parenthood - Dow, Dawn Marie (University of California Press, 2019)
"Informed by news stories, such as those of the fatal shootings of Oscar Grant and Trayvon Martin, and engaged with ongoing popular and academic discussions of work and family conflict, Mothering While Black makes significant contributions to the sociology of work and family, race and ethnicity, and gender and culture. Using the analytical lens of intersectionality, it demonstrates that the frameworks typically deployed in research on middle-class mothers and their families, which usually focus on the experiences of elite white mothers, do not adequately capture the experiences of African American middle-class and upper-middle-class mothers. Through sixty in-depth semistructured interviews with African American middle-class and upper-middle-class women, Mothering While Black distills the experiences of these contemporary mothers, revealing the cultural expectations and constraints that inform their approaches to parenting, work and family, and childcare. Through their accounts, this book demonstrates how race, class, and gender complicate their parenting concerns and strategies, and identifies three aspects of African American middle-class identity that study participants worked to foster in their children. Through this research, the book expands on and revises theories related to parenting, racial identity formation, and family and work conflict by complicating existing frameworks for understanding the cultural pushes and pulls that influence mothers' decision-making"--Provided by publisher.